(untitled) (Global Business Management Review (GBMR), 2022)
Key account management, which refers to serve the strategically important customers, has been acknowledged as an important seller initiated strategy in business to business relationship that impacts profoundly on the organizational performance. The study will examine the relationship between successful key account management and organizational performance. It will also investigate the influence of various antecedent factors on the key account management effectiveness. Using survey questionnaire, data in this study will be collected from Bangladeshi garments factory. Theoretical and practical implications of the study as well as suggestions for future research will be provided.